P134 The lymphatic system plays an important role in the migration of pathogenic: T-cells towards synovial joints and entheses in psoriasis. (21st February 2018) - Verhaegh, D; Prens, E; Mus, A; Asmawidjaja, P; Davelaar, N; Hofman, A; Jaquet, J-B; Kok, M; Tas, S; Yagita, H; Hazes, J; Lubberts, E; et al.
Abstract : Introduction: Psoriasis (PsO) is a common inflammatory skin disease that is characterised by acanthosis, oedema formation, immune cell infiltration, abnormal vascular proliferation, and remodelling of the lymphatic system. Up to ~30% of PsO patients are affected by psoriatic arthritis, a devastating form of arthritis, which leads to disability and deterioration of quality of life. Thusfar, the transition from PsO to PsA, particularly the factors that determine the propensity of pathogenic T-cells in psoriasis to colonise synovial membrane in joints and entheses are poorly understood. Lymphatic endothelial cells (LECs), core components of the lymphatic vascular system and lymph nodes, may control the transmission of pathogenic T-cells in PsO to other sites including synovial joints and entheseal regions by programming these T-cells in terms of their homing properties. Objectives: The focus of our proposal is to investigate whether LECs are capable of modulating the differentiation and homing receptor profile on CD4 memory T-cells. Methods: Human dermal lymphatic endothelial cells (LEC; 0.5×10 4 ), and fibroblast-like synoviocytes of a patient with PsA (FLS; 1.0×10 4 ) were pre-incubated for 3 days with PsA synovial fluid (PsA-SF; 0/10/20% v/v). Then, LEC or FLS were co-cultured with 2.5×10 4  allogeneic CD4 + CD45RO + CD25 - T-cells that were sorted from peripheral blood mononuclear cells (PBMC) of 3 healthy donors with or without stimulation with αCD3 (0.3 µg/ml) and αCD28 (0.4 µg/ml). Results: By means of flow-cytometry based phenotypical analysis, dermal LECs appear to suppress the generation of Th17 cells from stimulated CD4 memory T-cells of healthy donors, as compared to co-culture experiments involving synovial fibroblasts. Initial studies to the underlying mechanisms suggest that blocking the non-canonical NF-κB pathway downstream of the lymphotoxin beta receptor (LTβR) impairs the capacity of the LECs to suppress Th17 generation. In addition, Delta-like ligand 4 (DLL4) is differentially expressed in LECs and synovial fibroblasts after 3 days of co-culture. Earlier studies have shown that DLL4 may induce RORyt expression. Blocking DLL4 using a monoclonal antibody also impairs the capacity of the LECs to suppress Th17 generation. Conclusions: In our co-culture setup, LECs suppress Th17 generation from stimulated CD4 memory T-cells, and are thus directly involved in T-cell differentiation. The LTβR/non-canonical NF-κB pathway and downstream DLL4-Notch1/4 may be involved in LEC mediated modulation of T-cell homing and deserves further exploration. Disclosure of interest: None declared